Kedokteran Keluarga: Menumbuhkan Suasana Positif Dalam Keluarga Melalui Psikologi Kesehatan Untuk Mencapai Kesejahteraan Yang Optimal - Inge Wattimena (JURNAL WIDYA MEDIKA, 2018)
Family Medicine focuses on the family’s role in creating health holistically. One such way is through the implementation of Health Psychology which studies health etiology psychologically; encourages promotion of health, disease prevention, and healing processes; supports public health policies; and develops health care. Through Health Psychology, which in general observes health from a bio-psycho-social perspective, it is expected that optimal family wellness is achieved